2020
DOI: 10.1128/mcb.00377-20
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin-Derived HSP90 Inhibitors Are Synthetic Lethal with NRF2

Abstract: Activating mutations in KEAP1-NRF2 are frequently found in tumours of the lung, oesophageous and liver, where they are associated with aggressive growth, resistance to cancer therapies, and low overall survival. Despite the fact that NRF2 is a validated driver of tumorigenesis and chemotherapeutic resistance, there are currently no approved drugs which can inhibit its activity. Therefore, there is an urgent clinical need to identify NRF2-selective cancer therapies. To this end, we developed a novel synthetic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…Nrf2 is activated in many tumor types and such tumors often exhibit resistance to existing therapies resulting in poor patient outcomes [ 141 ]. This has led to the development of Keap1 knockout cell line screens for the identification of compounds that exhibit synthetic lethality with Nrf2 overexpression [ 142 , 143 ]. Compounds such as mitomycin C and quinone based Hsp90 inhibitors which are activated by NQO1 have been identified in screens for agents that induce selective toxicity to tumors with activated Nrf2 [ 142 , 143 ].…”
Section: Inducibility Of Nqo1 – Nrf2 and Ah Receptor Mediated Inductimentioning
confidence: 99%
See 2 more Smart Citations
“…Nrf2 is activated in many tumor types and such tumors often exhibit resistance to existing therapies resulting in poor patient outcomes [ 141 ]. This has led to the development of Keap1 knockout cell line screens for the identification of compounds that exhibit synthetic lethality with Nrf2 overexpression [ 142 , 143 ]. Compounds such as mitomycin C and quinone based Hsp90 inhibitors which are activated by NQO1 have been identified in screens for agents that induce selective toxicity to tumors with activated Nrf2 [ 142 , 143 ].…”
Section: Inducibility Of Nqo1 – Nrf2 and Ah Receptor Mediated Inductimentioning
confidence: 99%
“…This has led to the development of Keap1 knockout cell line screens for the identification of compounds that exhibit synthetic lethality with Nrf2 overexpression [ 142 , 143 ]. Compounds such as mitomycin C and quinone based Hsp90 inhibitors which are activated by NQO1 have been identified in screens for agents that induce selective toxicity to tumors with activated Nrf2 [ 142 , 143 ]. Nrf2 activation would increase tumor NQO1 levels leading to activation of either mitomycin C to reactive quinone methide metabolites capable of alkylating DNA and the generation of hydroquinone derivatives of geldanamycin quinones which are more active Hsp90 inhibitors [ 22 , 24 ].…”
Section: Inducibility Of Nqo1 – Nrf2 and Ah Receptor Mediated Inductimentioning
confidence: 99%
See 1 more Smart Citation
“…Baird et al showed that Nrf2 target genes metabolize the quinone-containing geldanamycin compounds into more potent HSP90 inhibitors. They can enhance their cytotoxicity while simultaneously restricting the lethal effect on cells with aberrant Nrf2 activity, resulting in cell death [ 34 ]. This is a different approach to understanding the interaction network between HSP and OS.…”
Section: Hsf Activation and Nrf2 Pathwaymentioning
confidence: 99%
“…NRF2-addicted cancers show constitutively upregulation of NRF2 target genes. A cell culture system was established in which KEAP1-deleted cells and KEAP1-expressing normal cells were cocultured, and their proliferation was monitored by the distinct colors of fluorescence [ 91 ]. Drug screenings that aim to identify synthetic lethal chemical compounds that specifically kill cancer cells with intrinsically high NRF2 activity have been identified.…”
Section: Roles Of Nrf2 In Cancer Progressionmentioning
confidence: 99%